Diagnostic analysis of touristic potentialities and environmental impacts in the Alagoas country/Análise diagnóstica de potencialidades turísticas e impactos ambientais no sertão de Alagoas - José Fábio Oliveira; Conceição Maria Dias de Lima (Universidade Estadual de Alagoas, 2020)
This research results from a proposal of reading places used and not used by tourism practice in the Sertão de Alagoas, considering that the tourist activity comprises relevant aspect with the discourse of regional development by the public power and that ends up often leaving aside the inherent environmental impacts. This research is justified by the need to understand tourism as an important phenomenon for recent changes in the Sertão de Alagoas, especially in the municipality of Delmiro Gouveia, regarding tourism infrastructure, organizational structure, dynamics and relative environmental impacts. This paper aims to identify the tourist attractions, the spatial uses and the environmental impacts related to the tourist activity in Delmiro Gouveia municipality, making a comparison between a tourist place (Rio da Cruz) and a non tourist place (Rio São José).